∫ (ln(x)/(x*(1+ln(x))^2) dx

use u = 1+ln(x) as the substitution du/dx = 1/xdx = x du ∫ (ln(x)/(x*(1+ln(x))^2) dx = ∫ ((u-1)x/ x(u^2)) du = ∫ (u-1)/(u^2) du

Answered by Jack B. Maths tutor

6733 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Prove that the squared root of 2 is an irrational number


Show how you can rewrite (x+1)(x-2)(x+3) into the form of ax^3 + bx^2 + cx + d


Find dy/dx at t=3, where x=t^3-5t^2+5t and y=2t^2


Of the following 4 equations, 3 of them represent parallel lines. Which is the odd one out?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences